Risks of digital transformation of the labour market of Belarus - Rachkevich, Viktoryia A. (Journal of the Belarusian State University. Economics, 2025)
The changes in the labour market due to digital transformation are summarised. Potential risks for the labour market that may accompany the process of digitalisation are presented. Empirical data reflecting what risks are relevant for the labour market of Belarus at this stage of socio-economic development are presented.